Representasi Kemiskinan dalam Novel Kembara Rindu karya Habiburrahman El Shirazy: Kajian Sosiologi Sastra - Pangestu, Elsa Namira; Zulfadhli (Universitas Negeri Padang, 2024)
This research aims to discuss the forms, causes, and effects of poverty as expressed in the novel Kembara Rindu. This research uses descriptive literary research methodology, by observing words, phrases, clauses, and sentences related to poverty in the novel. The data collection techniques used include reading and understanding the novel, recording relevant data, and organizing them based on the research questions. Data analysis consisted of several stages: (1) identifying data related to the form of poverty; the causes of poverty, and its impact in the novel, (2) analyzing the collected data, and (3) presenting conclusions related to the issue of poverty in the form of a thesis. The findings of this study reveal that the forms of poverty found in the novel are absolute and relative poverty. The factors that cause poverty are the low quality of the labor force, difficult access to capital ownership, low technological capabilities, and inefficient use of resources. The effects of poverty are unemployment, crime, school dropouts, and difficult access to health.